The empirical analysis of tengkolok Malay heritage - Jeapry, Ezzry Hafiq; Kamaruddin, Norfadilah; Rosli, Hafizah; Sulaiman, Sharunizam (GADING Journal for the Social Sciences, 2024)
The Malay Tengkolok has its unique significance as an ancient heritage, and it is essential to safeguard it against the risk of being lost to future generations or going extinct. Despite this, the Malay Tengkolok is sometimes worn incorrectly due to confusion over the ideals of art history and current trends. As a result, this research focused on the public's knowledge of the Malay Tengkolok and how to better understand the public's role in preserving the heritage of the Tengkolok history. To gather data for this research study, we analysed contextual documents, conducted a questionnaire survey with 150 public members, and conducted observations at the National Museum. The findings of this study showed that most participants agreed that the heritage of Tengkolok should be honoured by using a new medium. The majority of them chose social media platforms as the ones that could be used to have a more significant impact on honouring Tengkolok heritage, as shown by the fact that the study's results and the documentation of this Malay Tengkolok could also serve as a means of appreciating the rich legacy that the Malay people have inherited.